Fabrication and Characterization of High Molecular Chitosan Film with Hydrogel Gelatin. (Journal of Chemical Natural Resources, 2020)
The research on fabrication and characterization of high molecular chitosan film with hydrogel gelatin has been successfully conducted. High molecular chitosan was dissolved in a solution of 1% acetic acid and gelatin was dissolved with aquadest at ± 60 ºC. The formed chitosan and gelatin solution was poured into the glass plate glass and then dried in an oven at ± 50ºC for 24 hours. Volume number variations of chitosan and gelatin solution were 25% : 75%, 50% : 50%, 75% : 25%, respectively.The formed chitosan was characterized using tensile test, SEM, and FT-IR analysis. The tensile test results showed that film chitosan with no gelatin was 1.280 Mpa compared to the ratio between chitosan solution and gelatin solution were 25%: 75, 50%: 50%, and 75%: 25% which tensile test results were 2.156, 2.840, and 9.604 Mpa, respectively. The FTIR test also showed the difference between chitosan and chitosan-gelatin film functional groups where the band at 3433.29 cm-1, which indicated N-H groups of chitosan and changed to be OH groups in chitosan-gelatin film at 3653.18 cm-1 bands. This study also found that three films produced a relatively smooth surface and not rough.